Organic solid electrolyte material, silicon-based solid-state battery and preparation method and application thereof
By using high -end energy, the polymerization network to form a polymer network, prepare organic solid electrolytes, solve the problem of poor cycle performance of solid battery, and achieve higher cycle stability and battery life.
Patent Information
- Application Number
- CN202411291505.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The poor circulation performance of existing solid-state batteries leads to fast capacity decay and limited cycle life, which cannot meet long-term use needs, especially in areas such as electric vehicles and smart grids.
The high -end energy polymerization is adopted to form a highly elastic, high tough polymer network. The organic solid electrolytes that are gel -shaped through thermal curing reactions in situ, the volume changes of the volume of silicon negative materials are cushioned, and the battery is charged and discharged.
It significantly improves the cycle stability of the silicon -based solid -state battery, reduces the structural damage of the electrolyte material in the charging and discharge process, extends the cycle life of the battery, and enhances the stability of the capacity.
Smart Images

Figure CN118791655B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to an organic solid electrolyte material, a silicon-based solid-state battery, and a preparation method and application thereof. Background Art
[0002] Solid-state batteries, as a cutting-edge battery technology, have attracted much attention in recent years due to their advantages such as high energy density and high safety. However, despite the many theoretical advantages of solid-state batteries, their practical application still faces many challenges, among which poor cycle performance is one of the key issues that needs to be solved urgently.
[0003] The cycle performance of solid-state batteries, that is, the ability of the battery to maintain its initial capacity after multiple charge and discharge processes, is an important indicator for measuring the battery's service life. Unfortunately, the current cycle stability of solid-state batteries is generally poor, mainly manifested in rapid capacity decay and limited cycle life. After multiple charge and discharge cycles, the capacity of solid-state batteries tends to drop significantly and cannot meet long-term use requirements, which greatly limits its application potential in electric vehicles, smart grids and other fields that require long-term stable operation.
[0004] To give full play to the energy density advantage of solid-state batteries with high specific energy, the negative electrode adopts a silicon negative electrode with higher specific capacity, which is a suitable choice and future trend. The traditional negative electrode material is a graphite negative electrode material. Because graphite has the advantages of small volume change rate (<10%), low potential, stable structure and low cost during the lithiation process, it has always occupied the absolute market of negative electrode materials. In recent years, the market application end has increasingly higher requirements for the energy density of lithium batteries to increase battery life. Silicon has a reversible capacity of up to 4200mAh / g, so it is considered to be the next generation of lithium-ion negative electrode materials that are most likely to replace graphite negative electrodes and be widely used. However, silicon has a volume expansion of more than 300% during the charging and discharging process. The ultra-high volume expansion will cause the destruction of the electrolyte interface film, constantly exposing the fresh material surface, thereby continuously consuming the electrolyte, accelerating the attenuation of material performance and battery capacity, and making the silicon-based negative electrode material have poor cycle performance and has not been widely used in the market. In solid-state batteries, if a silicon negative electrode is to be equipped to give full play to the advantages of high energy density, the improvement of cycle performance is even more important.
[0005] Existing electrolyte materials cannot meet the requirements of high cycle life of lithium-ion batteries, especially solid-state batteries. This is because the volume expansion and contraction of silicon negative electrode materials during the charge and discharge process is large, and large volume changes will destroy the structure of the electrolyte. Once the internal structure of the electrolyte is unstable, the electrolyte material is very likely to undergo structural changes during the charge and discharge cycle, affecting the ion transmission efficiency and accelerating capacity decay.
[0006] Furthermore, the interface contact between the solid electrolyte and the electrode material is unstable. For organic solid electrolyte materials, the volume change inside the electrolyte after the curing reaction is not conducive to maintaining the interface wetting state before curing. This interface state is prone to degradation during the charging and discharging process, resulting in obstructed ion transmission, which in turn affects battery performance. Under the large expansion and contraction deformation stress of the silicon negative electrode, local cracks occur in the organic solid electrolyte material, and the interface with the electrode will deteriorate, destroying the internal structure of the battery and affecting the cycle stability. Limited by the cycle performance, solid-state batteries with silicon negative electrodes are currently mainly used in scenarios with low requirements for cycle life.
[0007] Therefore, in order to meet the requirements of high cycle life, it is necessary to further optimize and improve the structure of organic solid electrolyte materials, such as modifying and regulating the chemical structure of polymer monomers, giving play to the unique cross-linking structure of polymers, and developing organic solid electrolyte materials with higher structural stability, reducing structural changes during charging and discharging, and significantly buffering the volume expansion effect of silicon negative electrodes, so that solid-state batteries with silicon-based negative electrodes exhibit excellent cycle stability. Summary of the invention
[0008] The main purpose of the present invention is to provide an organic solid electrolyte material, a silicon-based solid-state battery, and a preparation method and application thereof, so as to overcome the defects that conventional electrolyte materials in the prior art have limited effect in improving the electrochemical cycle stability of solid-state batteries with silicon negative electrodes, and that solid-state electrolyte materials will undergo volume shrinkage changes during the in-situ curing process, resulting in poor interface contact with the electrode, which is not conducive to the effective use of the capacity of solid-state batteries.
[0009] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0010] An embodiment of the present invention provides a method for preparing an organic solid electrolyte material, which comprises:
[0011] The prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte is subjected to an in-situ thermal curing reaction to obtain a gel-like organic solid electrolyte;
[0012] Wherein, the high-functionality monomer has a structure as shown in formula (I):
[0013] ;
[0014] Formula (I)
[0015] wherein n1, n2, and n3 are independently selected from 1 to 3; R 1 -R 6 are independently selected from Ra, Rb or Rc, and R 1 -R 6 Cannot be the same structure at the same time, Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
[0016] The embodiment of the present invention also provides an organic solid electrolyte material obtained by the aforementioned preparation method.
[0017] The embodiment of the present invention also provides the use of the aforementioned organic solid electrolyte material in preparing a lithium battery.
[0018] The present invention also provides a method for preparing a silicon-based solid-state battery, which comprises:
[0019] Assembling a prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte into a battery system containing a positive electrode, a separator, and a negative electrode, and then performing an infiltration treatment and an in-situ thermal curing reaction to obtain a silicon-based solid-state battery;
[0020] Wherein, the high-functionality monomer has a structure as shown in formula (I):
[0021] ;
[0022] Formula (I)
[0023] wherein n1, n2, and n3 are independently selected from 1 to 3; R 1 -R 6 are independently selected from Ra, Rb or Rc groups, and R 1 -R 6 Cannot be the same structure at the same time, Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
[0024] The embodiment of the present invention also provides a silicon-based solid-state battery prepared by the aforementioned preparation method.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The present invention uses high-functionality monomers that can polymerize to form a highly elastic and tough polymer network that can withstand large internal stress, effectively buffer the large volume change of the silicon negative electrode material during the charge and discharge process, inhibit the structural damage of the electrolyte material during the charge and discharge process, and maintain the charge and discharge performance of the battery;
[0027] (2) The high-functionality monomers used in the present invention can be converted into organic solid electrolytes with a relatively small amount of addition, and can be efficiently cross-linked into a three-dimensional network. The high-density polymer network has a low volume shrinkage rate, so that the interface contact between the electrolyte and the electrode can be maintained in a good state before and after curing;
[0028] (3) The high-functionality monomer used in the present invention has a low viscosity and can be used in solid electrolyte materials to reduce the interface wetting problem caused by increased viscosity, improve the effective interface contact of the electrolyte material with the electrode, and improve the capacity utilization effect of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 is the infrared spectrum of monomer 1 in Example 1 of the present invention;
[0031] Figure 2 1 is a graph showing the cycle results of silicon-based button half-cells of Example 1 of the present invention and Comparative Example 1;
[0032] Figure 3 It is a high-rate cycle life curve diagram of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0033] In view of the defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Specifically, as one aspect of the technical solution of the present invention, a method for preparing an organic solid electrolyte material involves:
[0035] The prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte is subjected to an in-situ thermal curing reaction to obtain a gel-like organic solid electrolyte;
[0036] Wherein, the high-functionality monomer has a structure as shown in formula (I):
[0037] ;
[0038] Formula (I)
[0039] wherein n1, n2, and n3 are independently selected from 1 to 3; R 1 -R 6 are independently selected from Ra, Rb or Rc, and R1 -R 6 Cannot be the same structure at the same time, Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
[0040] In the present invention, the high-functionality monomer has a higher functionality, and the functionality of the monomer is a reactive acrylate group, which is between 6 and 11. The functionality refers to the number of functional groups in a monomer molecule that can participate in the reaction, which is directly related to the reactivity of the reactants and the structural characteristics of the products. The functionality determines the number of active points of the monomer molecule in the reaction, thereby affecting the reaction rate and reaction path. Generally speaking, the higher the functionality, the more active points the monomer molecule has in the reaction, the faster the reaction rate may be, and the greater the probability that the monomer molecule participates in the polymerization reaction and chain growth.
[0041] At the same time, monomers with high functionality are more likely to form highly cross-linked polymer network structures, enhancing the strength and elasticity of the polymer. The organic solid electrolyte corresponding to the monomers of this patent forms a gel after curing, and the Young's modulus E of the gel is in the appropriate range of 0.6-1MPa. If E is too small, cracks and collapse will occur under the expansion and extrusion of the silicon-based negative electrode. If it is too large, it will be too rigid, which is not conducive to buffering the volume strain during charge and discharge, the interface contact becomes worse, and it is not conducive to the movement of molecular chains and the conduction of lithium ions in the electrolyte.
[0042] The specific chemical structure of the high-functionality monomer in the present invention is as follows:
[0043] ;
[0044] Among them, n1, n2, and n3 take values of 1-3. The main chain of the monomer molecule contains an ester group, which connects the large-volume terminal groups at both ends. The ester group gives the monomer molecule a strong polarity, can interact with the electrolyte solvent molecules, and improve the conductivity. In addition, the ester group has a strong chemical bond energy, which effectively connects the large-volume terminal groups at both ends and improves the strength and elasticity of the gel.
[0045] Among them, R 1 -R 6 It can be Ra, Rb, Rc groups, but not all of them are the same, i.e. R 1 -R 6 It cannot be just one of Ra, Rb, and Rc, where Ra is:
[0046] ;
[0047] Rb is:
[0048] ;
[0049] Rc is:
[0050] ;
[0051] Among them, in the Ra, Rb, and Rc groups, the values of m, p, and q are 1-3.
[0052] In some preferred embodiments, the viscosity of the prepolymer liquid is 2-7 mPas.
[0053] In some preferred embodiments, the initiator includes an azo initiator; the azo initiator includes any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate, and is not limited thereto.
[0054] In some preferred embodiments, the electrolyte includes a lithium salt and a solvent.
[0055] Furthermore, the electrolyte includes the following components calculated by mass: 10-20% lithium salt and 80-90% solvent.
[0056] Further, the solvent includes any one or more combinations of dimethyl carbonate, ethyl methyl carbonate, ethyl propionate, ethylene carbonate, fluoroethylene carbonate, propane sultone, and vinyl sulfate, but is not limited thereto.
[0057] In some preferred embodiments, the mass ratio of the high-functionality monomer to the electrolyte is 1-5:95-99.
[0058] In some preferred embodiments, the mass ratio of the initiator to the high-functionality monomer is 0.3-3:100.
[0059] In some preferred embodiments, the temperature of the in-situ thermal curing reaction is 40-80°C.
[0060] In some preferred embodiments, the in-situ thermal curing reaction time is 12-72 hours.
[0061] In some preferred embodiments, the method for preparing the high-functionality monomer comprises:
[0062] Reacting two polyol substances with different dosage ratios with acrylic substances at 50-90° C. to prepare a first precursor and a second precursor;
[0063] Furthermore, the first precursor is reacted with an acid substance at 50-70° C., and then the second precursor is added and reacted at 70-90° C. to obtain a high-functionality monomer.
[0064] Further, the polyol substance includes any one or more combinations of 3,3-bishydroxymethyl-1,5-pentanediol, 2,2-bishydroxymethyl-1,4-butanediol, and 2,2-bishydroxymethyl-1,3-propanediol, but is not limited thereto.
[0065] Further, the acrylic substance includes any one or more combinations of acrylic acid, aminoacetyl formate acrylate, and 2,2-aminoethyl formate diacrylate, but is not limited thereto.
[0066] Furthermore, the acid substance includes any one or more combinations of malonic acid, succinic acid, and glutaric acid, but is not limited thereto.
[0067] Furthermore, the molar ratio of the polyol substance to the acrylic substance is 1:2-4.
[0068] Furthermore, the molar ratio of the first precursor, the acid substance and the second precursor is: 0.8-1.2:0.8-1.2.
[0069] The high-functionality monomer in the present invention is synthesized by an efficient and simple method, and has the characteristics of low energy consumption, no pollution, easy production, etc. The specific synthesis method is to mix 3,3-bis(hydroxymethyl)-1,5-pentanediol or 2,2-bis(hydroxymethyl)-1,4-butanediol and other polyols with acrylic acid or aminoacetyl formic acid acrylate, etc., add 0.2-2wt% of dibutyltin dilaurate as a catalyst, and stir the mixture at 50-90°C for 2-12h. The polyols and acrylic acid in two different proportions react to obtain two different precursors 1 and 2. The precursor 1 is first mixed, and stirred evenly with an acid reactant such as malonic acid, succinic acid or glutaric acid, and 0.2-2wt% of sodium formate or sodium benzoate is added as a catalyst. The mixture is reacted at 50-70°C for 2-6h. The precursor 2 is then added, stirred evenly, and 0.2-2wt% of sodium formate or sodium benzoate is added as a catalyst. The mixture is heated to 70-90°C for 6-12h. The mixture is cooled to room temperature, filtered, washed with deionized water 3 times, and distilled under reduced pressure to obtain the target monomer product.
[0070] In the infrared spectrum, 1760-1730 cm -1 、1640-1630 cm -1 、1200-1150cm -1 Absorption peaks appeared, corresponding to the characteristic absorption peaks of acrylate group, amide group and ester group, which proved the structure of the synthesized monomer.
[0071] The high-functionality monomer in the present invention has high functionality, and the polymer molecular chain has high strength and elasticity after the reaction. At the same time, the monomer contains a short chain of ethoxylated groups with a suitable number of repeating units, and the ether oxygen bond of the ethoxylated groups has a large molecular bond rotation angle, that is, a high degree of freedom, which can improve the flexibility of the molecular chain, so that the monomer has a slight linear structure, and the molecular chain after polymerization can have good flexibility; and the ether oxygen bond has a strong polarity, which can interact strongly with the carbonate solvent molecules and lithium salts in the electrolyte, which are also highly polar, so that the compatibility between the two is improved. In this patent, the main chain and the terminal group of the monomer are distributed with a suitable number of repeating units of ethoxylated groups, which can make the monomer and the electrolyte components extremely compatible. After the monomer is polymerized, the polymer molecular chain can absorb the electrolyte very well due to its great compatibility with the electrolyte, and play the effect of locking and retaining the liquid. However, if the number of repeating units of the ethoxylated groups is too large, the monomer viscosity will be large, the wettability to the electrode will be poor, and the ethoxylated groups will bring the application problems of being intolerant to high voltage and easy to oxidize under high voltage.
[0072] The high-functionality monomer in the present invention has a high functionality, the monomer molecular structure is spherical, there is less physical entanglement and shuttling between the monomer molecules, and the monomer molecules form a structurally stable polymer network after cross-linking, so that it has a relatively small volume shrinkage rate. After multiple tests, the organic solid electrolyte corresponding to the high-functionality monomer in the present invention has a low volume shrinkage rate after curing, which is 0.1-0.5%.
[0073] The relatively small volume shrinkage rate can make the volume change rate of the material smaller before and after polymerization, avoiding the interface degradation caused by the large volume change before and after polymerization. This is because, before heating and curing, the prepolymer liquid is liquid, which can better infiltrate the pores of the electrode particles and penetrate into the inner layer of the electrode, showing molecular-level contact. After heating and curing, the monomer molecules are transformed into polymer networks. Microscopically, the molecular structures are connected, and macroscopically, it is a phase transition, that is, a change from liquid to solid. If this transformation process brings about a large volume change, it will inevitably cause the local interface to be out of contact and the degree of infiltration to decrease, which is not conducive to the conduction of lithium ions between the electrolyte and the electrode at the interface, and thus cannot exert the effective capacity. As the electrochemical cycle proceeds, lithium ions cannot be conducted at cracks with poor electrical contact, resulting in polarization impedance, which will affect the stable performance of the battery capacity and lead to reduced cycle performance of solid-state batteries.
[0074] The high-functionality monomer in the present invention is a high-functionality monomer, each functionality is a reaction site, and the dense reaction sites give the monomer a higher reactivity, and can undergo polymerization reaction at a lower content and concentration to form a polymer network, which makes the mass proportion of the monomer in the electrolyte can be compressed to an extremely low level of 1-5%.
[0075] The prepolymer solution contains monomers, electrolyte and initiator. When the monomer is cured, an initiator needs to be added to initiate the polymerization reaction. The initiator of this patent is an azo initiator, such as azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, etc. The amount of initiator added is relatively low, generally 0.3-3 wt% of the monomer amount.
[0076] Since the monomers are polymerized to form bulk molecules, the movement of polymer chains is more difficult than that of small molecules in the electrolyte solvent and lithium salt anions and cations. Lithium ions are inevitably restricted under these conditions. A lower monomer content can keep the comprehensive ionic conductivity of the electrolyte at a high level of 5-10 mS / cm.
[0077] Another aspect of the embodiments of the present invention further provides an organic solid electrolyte material obtained by the aforementioned preparation method.
[0078] Furthermore, the Young's modulus E of the organic solid electrolyte is 0.6-1 MPa.
[0079] Furthermore, the ionic conductivity of the organic solid electrolyte is 5-10 mS / cm.
[0080] Another aspect of the embodiments of the present invention further provides use of the aforementioned organic solid electrolyte material in preparing a lithium battery.
[0081] Another aspect of an embodiment of the present invention further provides a method for preparing a silicon-based solid-state battery, comprising:
[0082] Assembling a prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte into a battery system containing a positive electrode, a separator, and a negative electrode, and then performing an infiltration treatment and an in-situ thermal curing reaction to obtain a silicon-based solid-state battery;
[0083] Wherein, the high-functionality monomer has a structure as shown in formula (I):
[0084] ;
[0085] Formula (I)
[0086] wherein n1, n2, and n3 are independently selected from 1 to 3; R 1 -R 6 are independently selected from Ra, Rb or Rc groups, and R 1 -R 6 Cannot be the same structure at the same time, Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
[0087] In some preferred embodiments, the viscosity of the prepolymer liquid is 2-7 mPas.
[0088] In some preferred embodiments, the initiator includes an azo initiator; the azo initiator includes any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate, and is not limited thereto.
[0089] In some preferred embodiments, the electrolyte includes a lithium salt and a solvent.
[0090] Furthermore, the electrolyte includes the following components calculated by mass: 10-20% lithium salt and 80-90% solvent.
[0091] Further, the solvent includes any one or more combinations of dimethyl carbonate, ethyl methyl carbonate, ethyl propionate, ethylene carbonate, fluoroethylene carbonate, propane sultone, and vinyl sulfate, but is not limited thereto.
[0092] Further, the lithium salt includes any one or more combinations of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, and lithium difluorooxalatoborate, but is not limited thereto.
[0093] In some preferred embodiments, the mass ratio of the high-functionality monomer to the electrolyte is 1-5:95-99.
[0094] In some preferred embodiments, the mass ratio of the initiator to the high-functionality monomer is 0.3-3:100.
[0095] In some preferred embodiments, the temperature of the in-situ thermal curing reaction is 40-80°C.
[0096] In some preferred embodiments, the in-situ thermal curing reaction time is 12-72 hours.
[0097] In some preferred embodiments, the temperature of the immersion treatment is room temperature.
[0098] In some preferred embodiments, the infiltration treatment time is 24-72 hours.
[0099] In some preferred embodiments, the negative electrode includes a silicon-based negative electrode, but is not limited thereto.
[0100] In the present invention, the monomer is introduced into the electrolyte and mixed to form an organic solid electrolyte prepolymer. After the prepolymer is heated and cured, an organic solid electrolyte is formed in a gel state. Before heating and curing, the viscosity of the prepolymer is crucial to its wetting of the internal pole piece of the battery, the interfacial electrochemical reaction of the active particles in the pole piece, the conduction exchange of charge and lithium ions on the interface, and the stable performance of the battery capacity. The monomer of this patent is introduced into the prepolymer, and the viscosity of the prepolymer is 2-7mPas.
[0101] Another aspect of an embodiment of the present invention further provides a silicon-based solid-state battery manufactured by the aforementioned manufacturing method.
[0102] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. This embodiment is implemented on the premise of the technical solution of the invention, and a detailed implementation method and specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments.
[0103] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.
[0104] Embodiment 1:
[0105] 1 mol of 3,3-bis(hydroxymethyl)-1,5-pentanediol was stirred evenly with 3 mol of acrylic acid, 0.5 wt% of dibutyltin dilaurate was added as a catalyst, and the mixture was stirred at 60°C for 6 hours to obtain precursor 1. Then 1 mol of 3,3-bis(hydroxymethyl)-1,5-pentanediol was stirred evenly with 2 mol of acrylic acid and 1 mol of aminoacetyl acrylate, 0.5 wt% of dibutyltin dilaurate was used as a catalyst, and the mixture was stirred at 60°C for 6 hours to obtain precursor 2. Then the above precursor 1 was stirred evenly with 1 mol of acid reactants such as malonic acid, 1 wt% of sodium formate was added as a catalyst, and the mixture was reacted at 60°C for 4 hours. Then 1 mol of the above precursor 2 was added and stirred evenly, 1 wt% of sodium formate was added as a catalyst, the mixture was heated to 80°C for 8 hours, and finally cooled to room temperature, filtered, washed with deionized water 3 times, and distilled under reduced pressure to obtain the target product monomer 1. The specific chemical structure of monomer 1 is shown below:
[0106] ;
[0107] Among them, n1, n2, and n3 are all 1, R 1 -R 5 It can be Ra group, R 6 is the Rb group, and the values of m and p are 1. The infrared spectrum of monomer 1 is shown in Figure 1 As shown. At 1728 cm -1 There is an absorption peak, which is the stretching vibration peak of the carbonyl group, which is the characteristic peak of the carbonyl group in acrylate, 1160cm -1 The CO stretching vibration peak of the methylene group in the acrylate is 1634 cm -1 is the stretching vibration of the amide group, 1263 cm -1 These infrared absorption peaks are the stretching vibrations of the ester groups and prove the chemical structure of the monomer materials.
[0108] 3g of monomer 1 and 0.03g of initiator azobisisobutyronitrile were dissolved in 97g of electrolyte. The specific components of 97g of electrolyte contained 52g of ethyl methyl carbonate, 16g of ethylene carbonate, 10g of fluoroethylene carbonate, 1g of propane sultone, 2g of vinyl sulfate, 10g of lithium hexafluorophosphate, 5g of lithium bis(fluorosulfonyl)imide and 1g of lithium difluorophosphate. They were mixed evenly at room temperature in a drying room (relative humidity below 2% and dew point below -40 ºC). The prepolymer solution was injected into the dry battery cell assembled with the positive and negative electrodes and the diaphragm, pre-sealed with a heat plastic sealing machine, left to stand at room temperature for 24h, then placed in a hot oven, slowly heated to 50°C and reacted for 24h. During heating, the prepolymer solution reacted inside the dry battery cell, and an organic solid electrolyte was obtained by in-situ thermal curing to prepare a silicon-based solid-state battery. The solid-state battery was charged and discharged to obtain the electrochemical cycle performance test results.
[0109] Embodiment 2:
[0110] The same preparation method as in Example 1 is adopted. Compared with Example 1, n1, n2, and n3 of Monomer 2 are all 1, R1-R5 can be Ra groups, R6 is Rc group, and m and q are 1. The specific chemical structure of Monomer 2 is as follows:
[0111] ;
[0112] The monomer 2, the initiator and the electrolyte are in-situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0113] Embodiment 3:
[0114] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 3 were all 1, and R 1 -R 4 It can be Ra group, R 5 , R 6 is the Rb group, m and p are 1, and the specific chemical structure of monomer 3 is as follows:
[0115] ;
[0116] The monomer 3, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0117] Embodiment 4:
[0118] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 4 were all 1, and R 1 -R4 It can be Ra group, R 5 , R 6 is the Rc group, m and q are 1, and the specific chemical structure of monomer 4 is as follows
[0119] ;
[0120] The monomer 4, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0121] Embodiment 5:
[0122] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 5 were all 1, and R 1 -R 4 It can be Ra group, R 5 is the Rb group, R 6 is an Rc group, m, p, q are all 1, and the specific chemical structure of monomer 5 is as follows:
[0123] ;
[0124] The monomer 5, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0125] Embodiment 6:
[0126] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 6 were all 1, and R 2 -R 5 It can be Ra group, R 1 is the Rb group, R 6 is an Rc group, m, p, q are all 1, and the specific chemical structure of monomer 6 is as follows:
[0127] ;
[0128] The monomer 6, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0129] Embodiment 7:
[0130] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 7 were all 1, and R 2 -R 5 It can be Ra group, R1 , R 6 is the Rb group, m and p are 1, and the specific chemical structure of monomer 7 is as follows:
[0131] ;
[0132] The monomer 7, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0133] Embodiment 8:
[0134] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 8 were all 1, and R 2 -R 5 It can be Ra group, R 1 , R 6 is an Rc group, m and q are 1, and the specific chemical structure of monomer 8 is as follows:
[0135] ;
[0136] The monomer 8, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0137] Embodiment 9:
[0138] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 9 were all 1, and R 2 -R 4 It can be Ra group, R 1 is the Rb group, R 5 , R 6 is an Rc group, m, p, q are all 1, and the specific chemical structure of monomer 9 is as follows:
[0139] ;
[0140] The monomer 9, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0141] Embodiment 10:
[0142] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 10 were all 1, and R 2 -R 4 It can be Ra group, R 1is an Rc group, R 5 , R 6 is an Rb group, m, p, and q are all 1, and the specific chemical structure of monomer 10 is as follows:
[0143] ;
[0144] The monomer 10, an initiator and an electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain an electrochemical cycle performance test result.
[0145] Embodiment 11:
[0146] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 11 were all 1, and R 2 -R 4 It can be Ra group, R 1 , R 6 is the Rb group, R 5 is an Rc group, m, p, q are all 1, and the specific chemical structure of monomer 11 is as follows:
[0147] ;
[0148] The monomer 11, the initiator and the electrolyte are in-situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0149] Embodiment 12:
[0150] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 12 were all 1, and R 2 -R 4 It can be Ra group, R 1 , R 5 is an Rc group, R 6 is the Rb group, m, p, q are all 1, and the specific chemical structure of monomer 12 is as follows:
[0151] ;
[0152] The monomer 12, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0153] Embodiment 13:
[0154] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 13 were all 1, and R 2-R 4 It can be Ra group, R 1 , R 5 , R 6 is the Rb group, m and p are 1, and the specific chemical structure of monomer 13 is as follows:
[0155] ;
[0156] The monomer 13, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0157] Embodiment 14:
[0158] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 14 were all 1, and R 2 -R 4 It can be Ra group, R 1 , R 5 , R 6 is an Rc group, m and q are 1, and the specific chemical structure of monomer 14 is as follows:
[0159]
[0160] The monomer 14, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0161] Embodiment 15:
[0162] The same preparation method as in Example 1 was used. Compared with Example 1, the n1 and n3 of monomer 15 were both 1, n2 was 3, and R 1 -R 5 It can be Ra group, R 6 is the Rb group, m and p are 1, and the specific chemical structure of monomer 15 is as follows:
[0163] ;
[0164] The monomer 15, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0165] Embodiment 16:
[0166] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 16 were all 1, and R 1 -R 5It can be Ra group, R 6 All are Rb groups, m is 3, p is 1, and the specific chemical structure of monomer 16 is as follows:
[0167] ;
[0168] The monomer 16, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0169] Embodiment 17:
[0170] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 17 were all 1, and R 1 -R 5 It can be Ra group, R 6 All are Rb groups, m is 1, p is 3, and the specific chemical structure of monomer 17 is as follows:
[0171] ;
[0172] The monomer 17, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0173] Embodiment 18:
[0174] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 18 were all 1, and R 1 All are Ra groups, R 2 -R 6 It can be an Rb group, m and p are 1, and the specific chemical structure of monomer 18 is as follows:
[0175] ;
[0176] The monomer 18, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0177] Embodiment 19:
[0178] The same preparation method as in Example 1 was used. Compared with Example 1, the n1, n2, and n3 of monomer 19 were all 1, and R 1 are all Rc groups, R 2 -R 6 It can be an Rb group, m, p, q are all 1, and the specific chemical structure of monomer 19 is as follows:
[0179] ;
[0180] The monomer 19, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0181] Embodiment 20:
[0182] The same preparation method as in Example 1 was used. Compared with Example 1, n1, n2, and n3 of monomer 20 were all 3, and R 1 -R 5 It can be Ra group, R 6 is the Rb group, m and p are 1, and the specific chemical structure of monomer 20 is as follows:
[0183] ;
[0184] The monomer 20, an initiator and an electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0185] Embodiment 21:
[0186] The same preparation method as in Example 1 is adopted, except that the mass proportion of monomer 1 is 5% compared with Example 1. The monomer, initiator and electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0187] Embodiment 22:
[0188] The same preparation method as in Example 1 is adopted, and the difference from Example 1 is that the electrolyte formula is different. 97g of the electrolyte contains 32g of ethyl methyl carbonate, 20g of dimethyl carbonate, 16g of ethylene carbonate, 10g of fluoroethylene carbonate, 1g of propane sultone, 2g of vinyl sulfate, 0.5g of tris(trimethylsilyl) phosphate and 10g of lithium hexafluorophosphate, 5g of lithium bis(fluorosulfonyl)imide, and 0.5g of lithium difluorooxalate borate. The monomer, the initiator, and the electrolyte are in-situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain an electrochemical cycle performance test result.
[0189] Embodiment 23:
[0190] The same preparation method as in Example 1 is adopted, except that azobisisoheptanenitrile is used as the initiator, the monomer, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, a silicon-based solid-state battery is prepared, the solid-state battery is charged and discharged, and the electrochemical cycle performance test results are obtained.
[0191] Embodiment 24:
[0192] The same preparation method as in Example 1 is adopted, and the difference compared with Example 1 lies in the in-situ curing process. The electrolyte solution is mixed and injected into the battery system, pre-sealed and left to stand at room temperature, soaked for 72 hours, and then heated and cured at 60°C for 20 hours to obtain a solid-state battery.
[0193] Comparative Example 1:
[0194] The same preparation method as in Example 1 is used, and the difference from Example 1 is that R 1 -R 6 All are Ra groups, n1, n2, and n3 are all 1, and m is 1. The specific chemical structure of monomer 21 is as follows:
[0195] ;
[0196] The monomer 21, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0197] Comparative Example 2:
[0198] The same preparation method as in Example 1 is used, and the difference from Example 1 is that R 1 -R 5 All are Ra groups, m is 10, n1, n2, n3 are all 1, R 6 All are Rb groups, p is 1, and the specific chemical structure of monomer 22 is as follows:
[0199] ;
[0200] The monomer 22, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0201] Comparative Example 3:
[0202] The same preparation method as in Example 1 is used, and the difference from Example 1 is that R 6 is an Rb group, p is 3, n1, n2, and n3 are all 1, R 1 -R5 It can be a Ra group, m has a value of 1, and the specific chemical structure of monomer 23 is as follows:
[0203] ;
[0204] The monomer 23, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0205] Comparative Example 4:
[0206] The same preparation method as in Example 1 is used. The difference from Example 1 is that n2 of monomer 24 is 10, n1 and n3 are both 1, and R 1 -R 5 It can be Ra group, R 6 All are Rb groups, m and p are 1, and the specific chemical structure of monomer 24 is as follows:
[0207] ;
[0208] The monomer 24, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0209] Comparative Example 5:
[0210] The same preparation method as in Example 1 is used. Compared with Example 1, the difference is that n2 of monomer 25 is 0, the main chain of the monomer has no ester group, n1 and n3 are both 1, and R 1 -R 5 It can be Ra group, R 6 All are Rb groups, m and p are 1, and the specific chemical structure of monomer 25 is as follows:
[0211] ;
[0212] The monomer 25, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0213] Comparative Example 6:
[0214] The same preparation method as in Example 1 was used. The difference from Example 1 was that R 6 is a methyl group, n1, n2, n3 are all 1, R 1 -R 5 It can be a Ra group, m has a value of 1, and the specific chemical structure of monomer 26 is as follows:
[0215] ;
[0216] The monomer 26, the initiator and the electrolyte are in situ thermally cured to obtain an organic solid electrolyte, and a silicon-based solid-state battery is prepared. The solid-state battery is charged and discharged to obtain electrochemical cycle performance test results.
[0217] The materials of the above-mentioned embodiments and comparative examples were subjected to comprehensive tests on physical and chemical properties, button-type half-cells, and soft-pack full-cells, and the test results are summarized in Table 1.
[0218] The test method used in the present invention is:
[0219] Infrared spectrum test:
[0220] Place the sample to be tested on the crystal surface of the optical platform of the infrared spectrometer ATR (model is20), open the infrared ATR test software, and set the test parameters, with a resolution of 4 and a scan number of 32. After starting the test instrument, rotate the knob above the reflector to deposit the sample to be tested so that it is fully in contact with the emission hole below, and start collecting data. After the test is completed, the infrared spectrum information of the sample can be obtained.
[0221] Viscosity test:
[0222] Use NDJ-5S digital display rotary viscometer to test the viscosity of organic solid electrolyte prepolymer. Pour the prepolymer into a flat-bottom container with a diameter greater than 60 mm. Maintain the prepolymer temperature at 25°C and keep the operating table stable and vibration-free. Screw the instrument protection frame into the lower end of the instrument in reverse direction. Use the L0 rotor to screw into the instrument universal joint counterclockwise. Rotate the lifting knob to slowly immerse the rotor in the prepolymer until the rotor liquid level mark, that is, the groove scale, is in the same plane as the liquid surface. Adjust the instrument level again. Press the rotor selection key, select the speed and press the OK key. The rotor starts to rotate. After the displayed value stabilizes, press the stop key to read the viscosity value.
[0223] Volume shrinkage test:
[0224] The density of the monomer before and after curing is measured with a densitometer, and the volume shrinkage is obtained based on the ratio of the density difference before and after curing to the original density before curing.
[0225] Conductivity test:
[0226] The electrode ring for fixing the electrolyte container and the polytetrafluoroethylene single ring acting as the electrolyte container are placed at the bottom of the battery shell, and then the prepolymer to be tested is dripped into the electrolyte container so that the electrolyte completely fills the chamber of the electrolyte container, and the stainless steel electrode plug is covered to form a blocking electrode; finally, the upper cover of the battery shell is covered, and the butterfly nut is tightened to complete the assembly of the battery. The assembled blocking battery is directly connected to the electrochemical workstation (VMP-3e, Bio-Logic) and placed in a 50℃ constant temperature box. The battery is cured at high temperature, and the AC impedance test is performed at a frequency of 1 MHz to 0.03 Hz. The battery is tested by EIS. According to σ=L / (R*S), σ is the ionic conductivity, L is the electrolyte thickness, S is the area of contact between the electrolyte membrane and the electrode, and R is the impedance measured by the impedance meter. The above formula is used to calculate the ionic conductivity (σ, mS / cm) of the solid electrolyte.
[0227] Young's modulus test:
[0228] Turn on the Mettler DMA850 instrument, select the constant strain test compression mode, use a titanium alloy compression test bench with a diameter of 10 mm, cut out a cylindrical organic solid electrolyte sample with a diameter of 6 mm and a height of 2 mm, test temperature 25 ° C, test frequency 1 Hz, constant compression 10 μm, initial stroke down 15 μm, last 10 minutes, use the DMA instrument supporting software to collect test data, take the average of the last 5 minutes of data as the output result, and obtain the Young's modulus E.
[0229] Silicon-based button battery test:
[0230] Silicon-carbon-graphite composite material: conductive glue: (CMC+SP): SBR was magnetically stirred in deionized water at a mass ratio of 95:1.5:1.5:2 for 8 hours to make it evenly mixed. The mixed slurry was coated on copper foil and dried in vacuum at 60°C as a working electrode. Metal lithium was used as the counter electrode and reference electrode, and the electrolyte was 1 mol / L LiPF 6 -EC (ethylene carbonate) / DMC (dimethyl carbonate) / EMC (ethyl methyl carbonate) (volume ratio of 1:1:1), CR2016 button battery assembly was completed in a glove box filled with high-purity argon, and 4 batteries were prepared for each group of samples.
[0231] The charge-discharge cycle test was conducted on a LAND battery tester. The battery was tested for 50 cycles with a voltage range of 0.005V to 1.5V. The first three cycles were activated by charging and discharging with currents of 0.1, 0.2, and 0.5C, and the fourth cycle was followed by a 1C charge-discharge cycle. The capacity retention rate was calculated after the cycle test, where the 50-cycle capacity retention rate = the 50th cycle discharge capacity / the 1st cycle discharge capacity*100%.
[0232] Silicon-based soft-pack full battery high-rate cycle test:
[0233] Silicon-based soft-pack full batteries use silicon-carbon material as the negative electrode material.
[0234] Positive electrode preparation method: grind and mix 80-95% of positive electrode active material and 1-10% of conductive agent acetylene black by mass, add 1-10% of polyvinylidene fluoride PVDF and 1-methyl-2-pyrrolidone NMP by mass, grind and mix to obtain positive electrode material, wherein NMP is used for mixing, dispersing and adjusting the viscosity of the slurry, and volatilizes during drying, so it is not included in the mass percentage of the positive electrode material; the positive electrode material is coated on the surface of aluminum foil and dried to obtain the positive electrode.
[0235] Preparation method of negative electrode sheet: add 80-95% silicon-carbon composite negative electrode material by weight to 1-10% conductive carbon black SP by weight, grind and mix, add 1-5% sodium carboxymethyl cellulose CMC by weight, 1-5% polystyrene butadiene copolymer SBR by weight and water, grind and disperse, mix, coat on the surface of copper foil, dry, and obtain negative electrode sheet. The diaphragm is a porous support material that isolates the positive and negative electrodes, and can be polyethylene diaphragm, polypropylene diaphragm, polytetrafluoroethylene non-woven fabric, etc.
[0236] The monomer content in the electrolyte is 1-5%, and the electrolyte content is 95-99%. The electrolyte formula is: the mass fraction of dimethyl carbonate, ethyl methyl carbonate, ethyl propionate and other solvents is 80-90%, and the mass fraction of lithium salt is 10-20%. The electrolyte solution is mixed and injected into the battery system of the positive electrode, separator and negative electrode, pre-sealed and left to stand at room temperature for 24-72 hours, and then heated and cured at 40-80℃ for 12-72 hours to obtain a solid-state battery.
[0237] Regarding the soft-pack full-battery rate cycle test system, the battery is first formed, charged with 0.02C constant current for 60 minutes, 0.05C constant current for 60 minutes, 0.1C constant current for 120 minutes, and 0.2C constant current for 180 minutes, with an upper limit voltage of 3.9V, and then charged with 3C constant current and constant voltage, and discharged with 1C current, that is, CC-CV mode for room temperature cycling, the charge and discharge cut-off voltage is 2.75-4.2V, and the battery high-rate cycle curve is obtained.
[0238] Table 1
[0239]
[0240] Figure 2It is a graph showing the cycle results of the silicon-based button half-cells of Example 1 (solid) and Comparative Example 1 (hollow) of the present invention. It can be seen that after 50 cycles of buttoning, the material of Example 1 has higher elasticity and toughness, can withstand the strain caused by the large volume expansion and contraction of the silicon-based particles during the charge and discharge process, alleviate the generation of crack gaps in the active particles, and keep the electrical contact of the active particle interface and the conductive network of the electrolyte itself relatively intact, thereby improving the cycle performance of the battery.
[0241] Figure 3 3 is a high-rate cycle life curve diagram of Example 1 (implemented) of the present invention and Comparative Example 1 (dashed line). It can be seen that the cycle life of the silicon-based solid-state battery corresponding to Example 1, that is, when the capacity decays to 80% of the original value, reaches 73 cycles, which is much better than 39 cycles of Comparative Example 1. This shows that the material of Example 1 can maintain normal operation inside the battery during high-rate charge and discharge at the full-battery level, that is, during the cycle process of rapid silicon-based lithium intercalation and volume change. The organic solid electrolyte of Example 1 can withstand the strain caused by volume change, buffer internal stress, greatly stabilize the internal electrochemical structure of the battery, and improve the battery cycle life.
[0242] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0243] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an organic solid electrolyte material, characterized in that: include: The prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte is subjected to an in-situ thermal curing reaction to obtain a gel-like organic solid electrolyte; Wherein, the high-functionality monomer has a structure as shown in formula (I): ; Formula (I) Wherein, n1, n2, and n3 are independently selected from 1 to 3; R1-R6 are independently selected from Ra, Rb, or Rc, and R1-R6 cannot be the same structure at the same time; Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
2. The preparation method according to claim 1, characterized in that: The viscosity of the prepolymer liquid is 2-7 mPas; And / or, the initiator comprises an azo initiator; the azo initiator comprises any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate; And / or, the electrolyte comprises a lithium salt and a solvent; And / or, the mass ratio of the high-functionality monomer to the electrolyte is 1-5:95-99; and / or, the mass ratio of the initiator to the high-functionality monomer is 0.3-3:100; and / or, the temperature of the in-situ thermal curing reaction is 40-80° C.; And / or, the in-situ thermal curing reaction time is 12-72 hours.
3. The preparation method according to claim 1, characterized in that: The preparation method of the high-functionality monomer comprises: Reacting two polyol substances with different dosage ratios with acrylic substances at 50-90° C. to prepare a first precursor and a second precursor; Furthermore, the first precursor is reacted with an acid substance at 50-70° C., and then the second precursor is added and reacted at 70-90° C. to obtain a high-functionality monomer.
4. The preparation method according to claim 3, characterized in that: The polyol substance includes any one or more combinations of 3,3-bishydroxymethyl-1,5-pentanediol, 2,2-bishydroxymethyl-1,4-butanediol, and 2,2-bishydroxymethyl-1,3-propylene glycol; And / or, the acrylic substance includes any one or more combinations of acrylic acid, aminoacetyl formate acrylate, and 2,2-aminoethyl formate diacrylate; And / or, the acid substance includes any one or more combinations of malonic acid, succinic acid, and glutaric acid; And / or, the molar ratio of the polyol substance to the acrylic substance is 1:2-4; And / or, the molar ratio of the first precursor, the acid substance and the second precursor is 1:0.8-1.2:0.8-1.
2.
5. An organic solid electrolyte material obtained by the preparation method according to any one of claims 1 to 4.
6. The organic solid electrolyte material according to claim 5, characterized in that: The Young's modulus E of the organic solid electrolyte is 0.6-1 MPa; and / or the ionic conductivity of the organic solid electrolyte is 5-10 mS / cm.
7. Use of the organic solid electrolyte material according to claim 5 or 6 in the preparation of lithium batteries.
8. A method for preparing a silicon-based solid-state battery, characterized in that: include: Assembling a prepolymer solution containing at least a high-functionality monomer, an initiator, and an electrolyte into a battery system containing a positive electrode, a separator, and a negative electrode, and then performing an infiltration treatment and an in-situ thermal curing reaction to obtain a silicon-based solid-state battery; Wherein, the high-functionality monomer has a structure as shown in formula (I): ; Formula (I) Wherein, n1, n2, n3 are independently selected from 1-3; R1-R6 are independently selected from Ra, Rb or Rc groups, and R1-R6 cannot be the same structure at the same time, and Ra is selected from , Rb is selected from , Rc is selected from , m, p, q are independently selected from 1-3.
9. The preparation method according to claim 8, characterized in that: The viscosity of the prepolymer liquid is 2-7 mPas; And / or, the initiator comprises an azo initiator; the azo initiator comprises any one or more combinations of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate; And / or, the electrolyte comprises a lithium salt and a solvent; And / or, the mass ratio of the high-functionality monomer to the electrolyte is 1-5:95-99; and / or, the mass ratio of the initiator to the high-functionality monomer is 0.3-3:100; And / or, the temperature of the infiltration treatment is room temperature; and / or, the time of the infiltration treatment is 24-72h; and / or, the temperature of the in-situ thermal curing reaction is 40-80° C.; And / or, the in-situ thermal curing reaction time is 12-72h; And / or, the negative electrode includes a silicon-based negative electrode.
10. A silicon-based solid-state battery prepared by the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Polymer electrolyte prepolymerization liquid, polymer electrolyte and electrochemical device
CN116525935A
Polymer electrolyte, its prodcing process and lithim bottery using the same electrolyte
CN1388172A